1998
DOI: 10.1023/a:1008812929476
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Commercial ceramics for dental computer aided design/computer aided manufacture (CAD/CAM) restorations suffer from surface chipping defects and microcracking. The influence of CAD/CAM machining of dental materials on the mechanical strength and extension of the damage zone was studied. Two different commercial dental ceramics, a feldspathic porcelain and a glass-ceramic, were CAD/CAM machined according to dental practice. The extension of the damage zone was analysed by a stepwise erosion of the surface, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Studies on subsurface damage in feldspathic porcelain and Dicor MGC glass ceramic revealed microcracking, chipping, crushing and crumbling. The response of Dicor MGC, a mica based glass ceramic, with CEREC-1 CAD CAM system and a high speed diamond wheel showed similar material removal mechanism of brittle fracture and micro-chipping to the experimental zirconia reinforced mica glass ceramic in the present study [58].…”
Section: Multiple Comparison Of Mean Differences Between Different Grsupporting
confidence: 72%
“…Studies on subsurface damage in feldspathic porcelain and Dicor MGC glass ceramic revealed microcracking, chipping, crushing and crumbling. The response of Dicor MGC, a mica based glass ceramic, with CEREC-1 CAD CAM system and a high speed diamond wheel showed similar material removal mechanism of brittle fracture and micro-chipping to the experimental zirconia reinforced mica glass ceramic in the present study [58].…”
Section: Multiple Comparison Of Mean Differences Between Different Grsupporting
confidence: 72%
“…Due to the brittle nature of ceramics, it is very likely that it will be more affected than metal [44]. Subcritical ceramic surface damage could develop in the form of surface microfractures, chipping defects, and altered surface quality [51, 52] and could constitute a point for crack propagation within the restoration under occlusal forces [52]. The extent of the damage is dependent on the material of the workpiece [53] and ranges from 15 to 60  μ m [5456].…”
Section: Computer-aided Production Streamsmentioning
confidence: 99%
“…According to Sindel et al [24] CAD/CAM machining of zirconia induces compressive stresses on the surface of the material. After machining of the material, the sintering process that follows partially heals microflaws and cracks created during machining [25].…”
Section: Discussionmentioning
confidence: 99%